2009
DOI: 10.1007/s10705-009-9316-1
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and carbon losses from dung storage in urban gardens of Niamey, Niger

Abstract: Intensive vegetable production in urban and peri-urban agriculture (UPA) of West African cities is characterized by high nutrient inputs. However, little is known about nitrogen (N) and carbon (C) losses in these systems, in particular during the storage of manure, the main organic fertilizer in these systems. We therefore aimed at quantifying gaseous emissions of ammonia (NH 3 ), nitrous oxide (N 2 O), carbon dioxide (CO 2 ) and methane (CH 4 ) as well as leaching losses of C, N, phosphorus (P) and potassium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 35 publications
2
30
1
1
Order By: Relevance
“…Similarly to soil fluxes, emissions from both sources are poorly constrained and according to the review by Owen and Silver (2015) data for dairy manure management are limited in Africa and extremely scarce for other systems (Predotova et al 2010). Yet in many countries, these sources are thought to be substantial contributors to total GHG budgets (Gerber et al 2013).…”
Section: Ghg Efmentioning
confidence: 99%
“…Similarly to soil fluxes, emissions from both sources are poorly constrained and according to the review by Owen and Silver (2015) data for dairy manure management are limited in Africa and extremely scarce for other systems (Predotova et al 2010). Yet in many countries, these sources are thought to be substantial contributors to total GHG budgets (Gerber et al 2013).…”
Section: Ghg Efmentioning
confidence: 99%
“…However, the latter was not used for goats in the studied farming system. Furthermore, the mode and duration of manure storage (Predotova et al, 2010;Rufino et al, 2007) strongly affect its N concentration. If despite these reservations an attempt is made to estimate the availability of goat manure to an average farm household in Masayrat keeping 20 adult goats of 30 kg live weight each and cropping 0.43 ha of land (Luedeling and Buerkert, 2008), 955 kg faecal OM yr À1 , equivalent to 2220 kg OM ha À1 yr À1 of manure would be available for this area, supplying 70 kg N ha À1 yr À1 and 12 kg P ha À1 yr À1 , and as such contributing substantially to the total nutrient removal of crops, which for the mountain oasis of Balad Seet was estimated to average 265 N ha À1 yr À1 and 33 P ha À1 yr À1 (Buerkert et al, 2005).…”
Section: Manure-based Nutrient Recyclingmentioning
confidence: 99%
“…However, dung is usually piling up in the courtyard without any cover and exposed to high temperatures during the hot dry season and to rainfall during the wet season. This management practice leads to substantial N losses through denitrification and NH 3 volatilization (Predotova et al, 2009) especially if the manure was to be utilized in farmers' home gardens and/or millet fields. Improved manure handling and storage by covering the dung heap with branches or plastic sheets could reduce nutrient losses (Rufino et al, 2007) in urban livestock production systems and thus reduce negative environmental externalities of such enterprises.…”
Section: Cattlementioning
confidence: 99%
“…Given that our study only determined the amount and quality of dung piling up uncovered in the courtyard, the monthly measuring interval has certainly lead to an underestimation of the nutrient excretion by livestock due to gaseous and eventual leaching losses occurring between excreta deposit and dung measurement. From a dung storage experiment in urban gardens of Niamey, Predotova et al (2009) reported gaseous N-losses to be highest during the hot dry season, which amounted to 1.1 mg/kg/day DM manure and leaching of 0.5 mg N/kg DM/ day, 0.7 mg P/kg DM/day DM and 17.1 mg K/kg DM/day during the rainy season when the manure is uncovered. Since the livestock farmers did not agree to use marker substances or faecal collection bags to determine feed intake and faecal excretion during grazing and at the homestead, nutrient inflow to the animal units through feed intake at pasture could not be accounted for in the calculation of NBs, although it might have been important.…”
Section: Cattlementioning
confidence: 99%